Promoting Breast Cancer Screening Take-Ups with Zero Cost: Evidence from an Experiment on Formatting Invitation Letters in Italy - Marco Bertoni; Luca Corazzini; Silvana Robone (Institute of Labor Economics (IZA), 2019)
We ran a randomized field experiment to ascertain whether a costless manipulation of the informational content (restricted or enhanced information) and the framing (gain or loss framing) of the invitation letter to the breast cancer screening program in Messina, Italy, affects the take-up rate. We show that giving enhanced loss-framed information about the risks of not having a mammography increases the take-up. This manipulation is especially effective among subjects with lower baseline take-ups – those living farther away from the screening site, residing in municipalities with low education, or with no recent screening experience – contributing to reduce socio-economic inequalities in screening. When we investigate the mechanisms behind our findings, we show that subjects exposed to our proposed manipulation are also less likely to postpone the appointment, signaling enhanced awareness about the risks related with delayed participation.
Keywords: C93; H51; I11; I18; 330; breast cancer screening; framing; information provision; randomized field experiment